Turbidite deposition in the Early Late Cretaceous Pindos Basin (External Hellenides) - NEUMANN, P. (Bulletin of the Geological Society of Greece, 2018)
The lower Upper Cretaceous clastic lithologies of the Pindos Zone in western Greece document a phase of enhanced tectonism. They are preserved as mixed carbonate/siliciclastic turbidite associations alternating with deep-marine siliceous sediments. New faunal and sedimentological data recovered from these deposits hint at two major pulses of turbidite shedding commencing at the change from the Early to the Middle Cenomanian and in the Late Turonian. The deposits are organized in generally thin clastic packages that can be attributed to lower fan facies. Different sources are likely for the occurrences in the central Pindos Mountains, the western and the easternmost Péloponnèse.